Assessment of knowledge, attitude, and practices on antibiotic use and its resistance among medical students in tertiary care teaching hospitals of Maharashtra - Dudhe, Bhushan; Kamdi, Nikhil; Giradkar, Akhil; Astankar, Poonam; Mankar, Nishikant; Ghotkar, Ulhas (Journal of Applied Pharmaceutical Research, 2023)
Background: One of the issues concerning public health today is the development and spread of antibiotic-resistant pathogenic microorganisms. The primary cause of this is the irrational use of these agents. To avoid antibiotic resistance, it is imperative to have correct knowledge of its rational use. This study was carried out among MBBS undergraduates who will work as healthcare providers in the future regarding their knowledge, attitudes, and practices about the usage of antibiotics and their resistance. Materials and Method: An online cross-sectional study conducted using Google Forms. A structured questionnaire was sent to medical students across Maharashtra. Data was acquired through responses to a self-administered questionnaire and analyzed with descriptive statistics. A one-way ANOVA test was applied to statistically compare students' knowledge levels based on their academic year. Results and Discussion: 344 students replied to Google Forms from eight medical institutes around Maharashtra. Regarding the usage of antibiotics, students' mean scores for knowledge, attitude, and practice were 6.03±1.46, 4.97±1.74, and 4.00±1.98, respectively. Of the total number of students, 234 (68.02%) had good knowledge, 134 (38.95%) had a good attitude, and only 43 (12.5%) had good practices for the usage of antibiotics. Students' knowledge levels varied significantly depending on the year they were studying. Conclusion: The present study indicates that medical students have a good degree of knowledge about antibiotic use and resistance. Improvement must be made regarding attitudes and practices.